Advokasi Stockpile Batubara Ilegal Oleh Walhi di Kota Padang - Wahyuni, Nila; Sabrani, Annisah; Hawilda, Lily; Pohan, Nur Latifa; Putri, Sintya Amalia; Suhaila, Siti (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
The coal industry in Indonesia is one of the most promising sectors, with trillions of rupiah in revenue each year. However, the rapid growth of this industry is not proportional to the risks it generates. Many coal companies still do not pay attention to their impact on the environment and society, such as the problem of illegal coal stockpiles. This illegal coal stockpile is a collection of coal that does not have official permission from the government to be mined, transported, and sold. This illegal practice can cause environmental and public health issues, such as air, soil, and water pollution, and potentially respiratory diseases and cancer. This research aims to explore and analyze the advocacy efforts undertaken by WALHI West Sumatra regarding the illegal coal stockpile conflict in Padang City. A qualitative approach with a case study was used in this research, applying the concept of advocacy developed by Sharma. Data were collected through interviews, observations, and documentation analysis. The results showed that WALHI West Sumatera had conducted various advocacy efforts, including investigations, socialization, education, campaigns, and legal advocacy to various related parties, such as the government, community, media, and business actors. As a result of these advocacy efforts, the Padang City Government has sealed several illegal coal stockpile operations. The Indonesian Ministry of Environment and Forestry is reviewing the case to take further steps to increase its authority in stockpile licensing. This study recommends that WALHI West Sumatera continue its advocacy efforts comprehensively while collaborating with various parties concerned about this environmental issue.